Amyloid beta accumulations and enhanced neuronal differentiation in cerebral organoids of Dutch-type cerebral amyloid angiopathy patients - Daoutsali, Elena; Pepers, Barry A.; Stamatakis, Stavros; van der Graaf, Linda M.; Terwindt, Gisela M.; Parfitt, David A.; Buijsen, Ronald A. M.; van Roon-Mom, Willeke M. C. (Frontiers in Aging Neuroscience, 2023)
Introduction ADutch-type cerebral amyloid angiopathy (D-CAA) is a hereditary brain disorder caused by a point mutation in the amyloid precursor protein (APP) gene. The mutation is located within the amyloid beta (Aβ) domain of APP and leads to Aβ peptide accumulation in and around the cerebral vasculature. There lack of disease models to study the cellular and molecular pathological mechanisms of D-CAA together with the absence of a disease phenotype in vitro in overexpression cell models, as well as the limited availability of D-CAA animal models indicates the need for a D-CAA patient-derived model. Methods We generated cerebral organoids from four D-CAA patients and four controls, cultured them up to 110 days and performed immunofluorescent and targeted gene expression analyses at two time points (D52 and D110). Results D-CAA cerebral organoids exhibited Aβ accumulations, showed enhanced neuronal and astrocytic gene expression and TGFβ pathway de-regulation. Conclusions These results illustrate the potential of cerebral organoids as in vitro disease model of D-CAA that can be used to understand disease mechanisms of D-CAA and can serve as therapeutic intervention platform for various Aβ-related disorders.